Upaya Meningkatan Pengetahuan Siswa/Siswi SMK Farmasi As-Shifa Ciparay Kelas XII Terkait Mencuci Tangan dengan 7 Langkah yang Baik dan Benar dengan Memakai Sabun: Pengabdian - Ahmad Zaelani; Indah Rifdailah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community outreach programme is part of the lecturers' obligations. The aim of this programme is to help the community realise the importance of washing their hands before and after doing something. The activity carried out at the As-Shifa Ciparay Pharmacy Vocational School was a health education session with the theme "Efforts to Increase the Knowledge of Students at the As-Shifa Ciparay Pharmacy Vocational School -Shifa Ciparay Regarding Handwashing with 7 Proper and Correct Steps Using Soap," as part of the community service programme. Through the process of this community service programme, awareness was raised among the community to care for their health and surroundings, particularly regarding handwashing with soap (CTPS) using 7 proper and correct steps. The analysis showed a p-value of 0.000, indicating the influence of health education on improving handwashing with soap using the 7 proper and correct steps on the understanding of students at SMK Farmasi As-Shifa Ciparay Class XII. An increase in the average score from the pretest (52.4) to the post-test (78.1) after the education session was also observed.